Employee experience –the missing link for engaging employees: Insights from an MNE's AI‐based HR ecosystem - Malik, Ashish; Budhwar, Pawan; Mohan, Hrishi; N. R., Srikanth (Human Resource Management, 2023)
AbstractAnalyzing multiple data sources from a global information technology (IT) consulting multinational enterprise (MNE), this research unpacks the configuration of a digitalized HR ecosystem of artificial intelligence(AI)‐assisted human resource management (HRM) applications and HR platforms. This study develops a novel theoretical framework mapping the nature and purpose of a digitalized AI‐assisted HR ecosystem for delivering exceptional employee experience (EX), an antecedent to employee engagement (EE). Employing the theoretical lenses of EX, EE, AI‐mediated social exchange, and engagement platforms, this study's overarching aim of this article is to establish how AI‐assisted HRM fits into an organization's ecosystem and, second, how it impacts EX and EE. Our findings show that AI‐assisted applications for HRM enhance EX and, thus, EE. We also see increases in employee productivity and HR function's effectiveness. Implications for research and practice are also discussed.